Future expectations on education and the labor of high school youth: Between the possible and desirable - Corica, Agustina (Última Década, 2020)
As part of the changes in the labor market and education system in recent years, this article aims to investigate expectations about future education and employment of young high school students from different social sectors in four jurisdictions of Argentina (city and province of Buenos Aires, Salta and Neuquén). For this purpose, a systematized forty-eight student interviews have been carried out on the junior middle school. The data analyzed were surveyed as part of the research project «Intersections between inequality and high school-an analysis of the dynamics of production and reproduction of social inequality-school in four jurisdictions». Among the main results is the existence of a gap between expectations and future prospects, and the shape of future representations about geographical and family support.